Mentoring Relationships Within a School-based Environment (Journal of School Administration Research and Development, 2024)
Past research examining mentoring programs has explained the benefits that student mentees received from having an adult as a mentor. For the mentee, studies indicate that mentoring relationships positively influence academic performance, social attitudes, communication abilities, and career aspirations. However, there has been very little research from the perspective of the mentor regarding their experiences of being in a mentoring relationship. This study builds upon Berning’s (2013) research that extracted the thoughts and opinions of retiree and teen mentors who worked with elementary students. The Berning report recommended that further research study adults involved in the workplace who spent their off time serving as mentors. This study addresses this gap by surveying 69 adult business professionals mentoring high school students in San Antonio, Texas. The survey revealed four central themes: 1) both mentors and mentees require high motivation for a successful relationship, with mentors often motivated by personal fulfillment; 2) mentors are driven by a commitment to give back to the community despite most lacking prior mentoring experience; 3) there is significant interest in mentor training to enhance program effectiveness; and 4) mentors generally enjoy the program, showing high willingness to continue, inclination to recommend it, and satisfaction with a monthly meeting schedule. Successful mentors are active listeners who engage their mentees by setting clear, aligned goals, while gaining the added benefits of enhanced communication and leadership skills through their mentoring roles.